The Role of Bandwagon Effect as an Intervening Variable in The Relationship Between Social Media Marketing and e-Wom on The Buying Interest of Potential Buyers Byfe Art Studio - Yolanda Febrina (Universitas Ciputra Surabaya, 2023)
This study aims to determine the role of bandwagon effect as an intervening variable in the relationship between social media marketing and eWOM on the buying interest of potential buyers of Byfe Art Studio. In this study there were 4 variables used and analyzed the relationship between variables including the mediation relationship. The variables in question are social media marketing, eWOM, bandwagon effect, and buying interest. The results of the analysis can later be used by Byfe Art Studio to improve social media marketing performance and increase potential buyers' buying interest. Researchers use quantitative types of research. In this study, there were as many as 179 people used as samples. The data analysis technique used is the structural model equation with the partial least square (PLS-SEM) method. The tool used as a data analysis instrument is the SMARTPLS program. The results of this study are that ocialmedia marketing affects eWOM, the formation of bandwagon effect, and potential buyer buying interest, eWOM affects the formation of bandwagon effect but does not affect potential buyer buying interest , bandwagon effect influence on buying interest and be able to mediate the relationship between eWOM and buying interest , but unable to mediate the relationship between social media marketing and potential buyer buying interest